An Unexpected Case of Intrapartum Pneumomediastinum - Drishti Madhok; Vinayak Smith; Erik Gunderson (Hindawi Limited, 2019)
The dyad of spontaneous pneumomediastinum and subcutaneous emphysema is collectively known as Hamman's syndrome. This rare complication is known to occur during the intrapartum period and its aetiology has been linked to the Valsalva maneuver in the second stage of labour. Nitrous oxide inhalation increases the risk. We present the case of a 21-year-old healthy woman who experienced these symptoms after nitrous oxide inhalation during the second stage of labour.